Aspectos jurídicos e ambientais da gestão de resíduos sólidos urbanos na Região Metropolitana de Aracaju - Costa, Sandro Luiz da (2010)
In pursuit of sustainable development there is a growing concern over solid waste policies to promote an integrated and participatory management system and activities that maximize the reuse and recovery, incorporating recycling and composting of waste and reintroducing them in productive chain. This research aims to demonstrate and assess the legal aspects and environmental management of municipal solid waste (MSW) in the metropolitan area of Aracaju (MRA), comprising the cities of Aracaju, Nossa Senhora do Socorro, São Cristóvão and the Barra dos Coqueiros within a holistic view and under the legal and rational approach of environment. To reach it was to raise the MSW regulations in Brazil and actions technical, legal and social control of MSW management in the MRA. For this, besides the documentary research, interviews were effective with the involved segments and visits to places of disposal of MSW and treatment of MRA. As a result, besides the compilation of the MSW legal system and environmental in Brazil and the retrospective of MSW management in the MRA in the past decades, observed that there is a legal sustainability as a rule of norms in the MRA and the municipalities of Sergipe, referring to the legal-ambient microsystems of RSU in the scope of these federative spheres. About MSW management, it was found that while sustainability is the rule, there are initial actions and even consolidated, as in the common collection and transportation of MSW, for the search of the sustainability of the system.